(3OjhGf CHj HcQ jMji Hf eMeO GdLRGQ GdSQbSWis - (3CHhHcQ jMji Hf eMeO GdLRGQ Hf YjSi GdSQbSWjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QC GdEfSGf Ndb hCLQi GddSGf HGdHjGf hHYO aEf GdTYQ deG cGf OjhGf GdYQH s
(3BNQgG (B:s
(3BNQ GdehLhO efg JbGS SGYI ajgG cjhe hef Whd GdSQi TgQkG cYGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs